Transversus Abdominal Plane Block for Postoperative Analgesia: A Systematic Review and Meta-analysis of Randomized-Controlled Trials. Issue 1 (February 2017) - Brogi, E.; Kazan, R.; Cyr, S.; Giunta, F.; Hemmerling, T. M.
Abstract : (Abstracted from Can J Anaesth, 2016;63(10):1184–1196) In order to evaluate the increasing amount of literature on the use of various transversus abdominis plane (TAP) block techniques in postoperative pain management, a meta-analysis and review of randomized controlled trials (RCTs) was done. The US National Library of Medicine, the Excerpta Medica, and the Cochrane Central Register of Controlled Clinical Studies databases were examined for the period January 1, 2004, to August 31, 2014, and 51 RCTs that satisfied the inclusion criteria of the meta-analysis were identified.